2020
DOI: 10.1097/ftd.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

Is Salivary Busulfan the Cause of Oral Mucositis and the Changes in Salivary Antioxidant Enzymes After Hematopoietic Cell Transplantation?

Abstract: Background: To determine whether the busulfan (Bu) present in saliva during hematopoietic cell transplantation (HCT) conditioning correlates with oral mucositis and the changes in salivary antioxidant enzymes. Methods: Bu levels in the plasma and saliva of 19 patients who received HCTs were quantified. Salivary flow and salivary superoxide dismutase and catalase activities were measured during HCT. For the toxicity analysis of salivary Bu, an in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
3
5
1
Order By: Relevance
“…Due to faster drug metabolization and rapid distribution, children displayed a higher clearance than adults, which led to lower busulfan AUC 0-∞,p in pediatric patients. Using a target AUC 0-∞,p range of 900-1500 μmol • min/L at each dose (European Medicines Agency recommendation), 23 patients (62.2%) could achieve the therapeutic window, which was consistent with the results (40%-60%) of Rhee et al, 29 but lower than those (78% and 76%) reported by Michel et al 30 Several investigators [16][17][18] have demonstrated the feasibility and accuracy of saliva TDM in busulfan. There was a significant correlation between busulfan concentration in the plasma and saliva (r = 0.87, p < .01), which is similar to the previous research by Rauh et al 16 (r = 0.96), de Paula Eduardo et al 18 (r = 0.92), and Bezinelli et al 17 (r = 0.97).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Due to faster drug metabolization and rapid distribution, children displayed a higher clearance than adults, which led to lower busulfan AUC 0-∞,p in pediatric patients. Using a target AUC 0-∞,p range of 900-1500 μmol • min/L at each dose (European Medicines Agency recommendation), 23 patients (62.2%) could achieve the therapeutic window, which was consistent with the results (40%-60%) of Rhee et al, 29 but lower than those (78% and 76%) reported by Michel et al 30 Several investigators [16][17][18] have demonstrated the feasibility and accuracy of saliva TDM in busulfan. There was a significant correlation between busulfan concentration in the plasma and saliva (r = 0.87, p < .01), which is similar to the previous research by Rauh et al 16 (r = 0.96), de Paula Eduardo et al 18 (r = 0.92), and Bezinelli et al 17 (r = 0.97).…”
Section: Discussionsupporting
confidence: 79%
“…Using a target AUC 0-∞,p range of 900-1500 μmol • min/L at each dose (European Medicines Agency recommendation), 23 patients (62.2%) could achieve the therapeutic window, which was consistent with the results (40%-60%) of Rhee et al, 29 but lower than those (78% and 76%) reported by Michel et al 30 Several investigators [16][17][18] have demonstrated the feasibility and accuracy of saliva TDM in busulfan. There was a significant correlation between busulfan concentration in the plasma and saliva (r = 0.87, p < .01), which is similar to the previous research by Rauh et al 16 (r = 0.96), de Paula Eduardo et al 18 (r = 0.92), and Bezinelli et al 17 (r = 0.97). The busulfan saliva concentrations were lower than plasma concentrations (C max,p = 1.19 ± 0.25 μg/mL, C max,s = 1.07 ± 0.22 μg/mL), with the S/P ratio close to 0.89.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, a correlation between BU concentrations in oral fluid and the occurrence of severe mucositis has been reported, and this could represent a useful application of oral fluid analysis. 27 In our study, all enrolled patients presented oral mucositis (71.4% grade 2 and 27.6% grade 3); however, the small number of observations does not allow any conclusions to be made in terms of the relationship with BU concentrations in oral fluid.…”
Section: Discussionmentioning
confidence: 68%